International Criminal Law, Humanitarian Law and Refugee Law From The Perspective of Human Rights Law - Dóra Szikszai, Laura Kovács-Berényi; Béres, Nóra (2026)
The  book  serves  as  a  textbook  for  the  Human  Rights  and  Rule  of  Law  LL.M.  programme  on  the  first place.  As  its  title  –  International  Criminal  Law, Humanitarian Law and Refugee Law from the Perspective of Human Rights Law – suggests, the volume focuses on those branches of international public law that are closely related to human rights law, and assists readers in getting a comprehensive overview on supplementary but significant segments of international public  law  that  might  also  come  into  play  when  it  comes  to  discussing  and  solving  human rights problems.  Therefore, the  book  primarily  serves  educational  purposes  to  navigate Human Rights and Rule of Law LL.M. students in understanding the key definitions and fundamental functioning of international human rights law’s border areas; (in synthesising their previously acquired knowledge on human rights; in introducing supplementary definitions that are of special significance when facing human rights issues; and all in all, in giving a whole landscape on these inter-related segments of international public law, in addition to granting considerable and complex knowledge on human rights.  Thus, the ultimate aim of this book is to provide  the  readers  with  a  thorough  analysis  on  certain branches  of  international  public  law  that  have  a  strong  relationship  with  international  human  rights  law:  international criminal law, international humanitarian law and international refugee law.  Throughout  the pages  of  this  book,  an  overview  is  offered  on  the  history  of  international  criminal  law,  on  international  crimes,  on  the  International  Criminal  Tribunal  for  the  Former  Yugoslavia  and  the  International  Criminal  Tribunal  for  Rwanda, on the International Criminal Court, on the history of humanitarian law, on the principles of humanitarian law (the principle of humanity, the principle of military necessity,  the  principle  of  distinction  and  the  principle  of  proportionality),  on  the 1949 Geneva Conventions and their Additional Protocols I-III, on the distinction between migration law and refugee law as well as between the terms of “migrant” and “refugee”, on the 1951 Convention Relating to the Status of Refugees, on the principle of non-refoulement, and on some specific Central and Eastern European characteristics.